First Report of ‘Candidatus Phytoplasma australasia’ Strain Related to Witches’-Broom of Tomato in Türkiye - Mustafa USTA; Abdullah GÜLLER; Hikmet Murat SİPAHİOĞLU (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
Phytoplasmas are dangerous bacteria severely infecting agricultural production worldwide. In the present study, the identification of phytoplasmas infecting tomato plants showing symptoms such as small leaves, flower abnormalities, stunting, witches' broom, and reddening was performed. Five plants, two symptomatic and three asymptomatic, were tested to verify phytoplasma infection. Total DNA isolated from 5 leaf samples was used as a template for PCR reactions. The phytoplasma agents were confirmed in the two symptomatic samples. BLASTn search of 16S rRNA of two sequences shared identity similarity of 99.84% with ‘Candidatus Phytoplasma australasia’. Computer-simulated virtual RFLP profiles show that the 16S rRNA sequences is identical to the reference pattern of the 16SrII-D subgroup, with a similarity coefficient of 1.00. Based on BLAST, virtual RFLP, and phylogenetic dendrogram, the identified phytoplasma strains are enclosed in the 16SrII-D subgroup. This is the first report of tomato witches' broom disease related to 16SrII-D subgroup phytoplasma strains in the Antalya province of Türkiye.